Isolation &Identification of Proteus spp. bacteria isolated from Locally processed raw Beef in Baghdad City - Maha Tareq Mohammed; Ahmed Husam Al-Deri (Journal of Kerbala for Agricultural Sciences, 2024)
This study was done to demonstrate the bacterial contamination of many type of raw Beef meat products that processed locally in Iraq by Proteus. spp. bacteria , during January to June from 2022 one hundred fifty Beef products samples ((burger, meatball, pasterma ) were randomly purchased from different local markets in Baghdad City ,These samples were sent to the Lab. of Microbiology for bacterial identification which performed by using different selective media like MacConkey Agar, blood agar, XLD agar, more identification was done by using Gram stain technique and biochemical tests , (11) isolates of Proteus spp. as (7.33%) was diagnosed and confirmed as Proteus mirabilis using VITEK 2 compact technique & Finally the Nucleotide Sequence of 16S rRNA Gene of isolated bacterial spp. was identified by PCR technique.